Volatile Profiling of Root-Shoot and Fruits of Capsicum frutescens var. Salo Dua from Enrekang, Indonesia - Nur, Fatmawati; Meriem, Selis (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Capsicum frutescens var. Salo Dua is a local variety cultivated in Enrekang Regency, South Sulawesi. It has unique traits of color transition during fruit ripening and extended post-harvest shelf life. However, the metabolite profiling in this potential variety has not been explored. This was an initial study that aimed to profile the volatile compounds in the root-shoot parts (as vegetative) and in the ripe fruits of Salo Dua variety. The instrument of Gas Chromatography coupled with Mass Spectrometry (GC-MS) was used to separate and characterize the volatile compounds. Our study revealed a higher number of forty-two volatiles in the ripe fruits compared to the twenty-eight volatiles in the shoot-root parts. The five major compositions of the chemical class in ripe fruits were characterized by the formation of alcohols (26%) followed by esters (19%), alkaloids (10%), fatty acids (10%), and ketones (7%). While the abundant volatiles in the root-shoot parts were shown by the presence of esters (29%), alcohols (21%), fatty acids (18%), alkaloids (11%), and heterocyclic (7%). There were nineteen volatiles that only emitted in the ripe fruits. Of which, capsaicin and dihydrocapsaicin were detected in the ripe fruits with an average relative area of 1% and 0.51%, subsequently.